Survey of the sexual satisfaction and the prevalence of marital infidelity (online and sexual) in the Iranian population - Shadgahraz, Samaneh; Ataran, Elnaz; Khodadadijokar, Farnaz; Abdollahi Moghadam, Maryam; Majidi Moemen Abad, Amir Hossein (Psychology of Woman Journal, 2022)
The quality of spouses’ relationships is the basis of the health or illness of the individual, family, and society. Therefore, study efforts can predict and control possible problems in this field. Thus, in the present study, the survey of sexual satisfaction and the prevalence of marital infidelity (online and sexual) in the Iranian population was discussed. The research method was a descriptive-survey. The statistical population was all Iranian married men and women living in Iran, who were selected from this community and by multi-stage cluster sampling in four provincial capitals. Then, according to Morgan’s sampling table, a proportional number of participants were taken from each center of the province, and their total was 1208 participants. Finally, the participants were examined by answering a few simple questions. Also, after mixing and classification, the frequency technique was used for experimenting and analyzing the data. The results showed that 204 participants (17.3 percent) were unsatisfied with sex with their spouses. Also, 189 participants (16 percent) reported online cheating, and 78 participants (6.6 percent) reported sexual cheating by their spouse. In this study, only the amount of online and sexual infidelity that the spouses were aware of was determined. Therefore, considering the importance of sexual satisfaction in consolidating the family structure and marital infidelity in its collapse, organizational planning by managers and mental health experts in the form of preventive and reformative programs seems necessary